2018
DOI: 10.22161/ijeab/3.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perception and Adoption of Agroforestry Practices in Faridpur District of Bangladesh

Abstract: This study mainly focused on exploring perception of farmers' towards agroforestry practices and identifying the demographic factors influencing agroforestry adoption in Faridpur district. Field survey was conducted during November-December, 2016 using semistructured questionnaire. Multi-stage random sampling was used to select upazillas, unions and villages. Snowball purposive sampling was applied to select 84 respondents in total for the questionnaire survey. Chi-square was used to test variables at 5% level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…Therefore, Sharmin and Rabbi [54] stated that in Jhenaidah district, 32% respondents are now practicing woodlot plantation, and this may be due to massive demand of local wood. Similar study by Saha et al [50] showed 13.09% respondents practiced woodlot plantation. On the contrary, Chakraborty et al [4] stated that, cropland agroforestry is a land based production system that is directly related to food security, employment, income opportunities and environmental issues which also plays a vital role in rural socio-economic development as well as poverty reduction.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, Sharmin and Rabbi [54] stated that in Jhenaidah district, 32% respondents are now practicing woodlot plantation, and this may be due to massive demand of local wood. Similar study by Saha et al [50] showed 13.09% respondents practiced woodlot plantation. On the contrary, Chakraborty et al [4] stated that, cropland agroforestry is a land based production system that is directly related to food security, employment, income opportunities and environmental issues which also plays a vital role in rural socio-economic development as well as poverty reduction.…”
Section: Discussionsupporting
confidence: 75%
“…Gautam et al [13] reported that homegarden contributed 60% of total consumption of agroforestry in India. Saha et al [50] found that homestead agroforestry is the most common agroforestry practice (39.28%) in Faridpur, Bangladesh. Another study conducted in north-eastern Atlantic forest biome in Brazil by Klie [38] revealed that most of the farmers (89%) working with agroforestry systems generates more income than working with conventional agriculture and they also showed positive views on livestock under tree crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three factors related to farmers' demographic characteristics, we found that age did not have a significant impact on their knowledge and perceptions. Similarly, several other studies conducted in different parts of the world found that age did not affect farmers' perception levels [70][71][72]. However, recent studies conducted in Indus River Basin of Pakistan and Bangladesh reported that younger farmers were more interested in the adoption of AF than old farmers as they are more knowledgeable about the benefit of applying advanced technology in farming such as AF [23,73].…”
Section: Factors Affecting Perceptions Of the Respondentsmentioning
confidence: 84%
“…Agroforestry merupakan sebuah nama kolekif sistem pengelolaan lahan yang mengintegrasikan tanaman berkayu dengan tanaman pertanian dan atau ternak dalam satu unit lahan sehingga terjadi interaksi ekologi dan ekonomi di antara semua penyusunnya (Santoro et al, 2020). Pemanfaatan lahan dengan sistem agroforestry dapat mengoptimalkan manfaat sosial, ekonomi, dan ekologi lahan secara berkelanjutan (Murthy et al, 2017;Saha et al, 2018;Pasaribu et al, 2019;Saputro et al, 2020). Secara ekonomi, agroforestry bermanfaat untuk meningkatkan persediaan bahan pangan dan energi untuk manusia, meningkatkan pendapatan petani, meningkatkan produktivitas lahan, menumbuhkan ekonomi kreatif masyarakat, mendukung pemenuhan masyarakat terhadap sandang, pangan, dan papan serta memenuhi kebutuhan berjenjang petani (Alao & Shuaibu, 2013;Olivi et al, 2015;Pasaribu et al, 2019;Sobolo et al, 2015).…”
Section: Pendahuluanunclassified